Beneficial Effect of Rosmarinic Acid on Neurobehavioral Deficits Induced by L-methionine in Adult Rats - Chaithum, Jirawadee; Dornlakorn, Oabnithi; Sritawan, Nataya; Aranarochana, Anusara; Umka Welbat, Jariya; Sirichoat, Apiwat (Srinagarind Medical Journal, 2024)
Background and Objective: Food consumption that contains large quantities of L-methionine (L-met), an essential amino acid can cause oxidative stress by increasing levels of homocysteine. High levels of homocysteine contribute to neuronal cell damage, which can lead to memory impairment. Rosmarinic acid (RA) is a phenolic compound widely distributed in rosemary, thyme and basil. Several studies revealed that rosmarinic acid has the ability to enhance learning and memory function. Therefore, this study was designed to determine the neuroprotective effect of rosmarinic acid against L-methionine-induced memory impairments. Methods: Male Sprague Dawley rats were divided into 6 groups: control, L-met (1.7 g/kg), RA (10 and 30 mg/kg) and L-met + RA (10 and 30 mg/kg) groups. Subjects were treated once a time per day for 28 days. Body weight was recorded every day. Before and after drug administration, spatial and recognition memory were investigated using the novel object location (NOL) and the novel object recognition (NOR) tests, respectively. Results: The results revealed that rosmarinic acid and L-met did not have a negative effect on the body weight and locomotor activity. Whereas NOL and NOR tests revealed that control, RA (10 and 30 mg/kg), L-met + RA (10 and 30 mg/kg) groups were significantly different in the time spent exploring between the familiar and novel location or object compared with the L-met group. Conclusion: This study demonstrates that rosmarinic acid had a protective effect against memory impairment induced by L-met.